The creative path of a teacher and scientist: to the 85th anniversary of H.I. Bakov - Lyudmila, Khavzhokova (Kavkazologiya, 2025)
The article presents a panoramic picture of the life and creative work of the literary scholar, teacher, Doctor of Philology, Professor Khangeri Ilyasovich Bakov. His contribution to education, science, national literary criticism, criticism, and journalism is noted. A review analysis of the researcher's scientific and scientific-critical works (monographs, collections of articles, chapters and sections in collective publications, etc.) is carried out, indicating the main areas of his activity. The article uses the biographical method, as well as the methods of observation, description, analysis, which made it possible to consider various aspects of the life of Kh.I. Bakov. The results obtained can be used in studying the history of the Adyghe ethnic group, national culture and literature; compiling reference, biobibliographic, encyclopedic publications; developing special courses on various issues of Adyghe literary criticism as a significant fragment of domestic philological science.